Isotretinoin-Induced Facial Hyperpigmentation: Idiosyncratic Reaction? - Halawi Ali; Abbas Ossama (Journal of Dermatologic Research And Therapy, 2015)
Isotretinoin is notorious for having a myriad of mucocutaneous side effects including cheilitis, xerodermia, facial erythema, pruritis, hair thinning, and brittle nails, among others. Although photosensitivity is considered to be one of the side effects of oral isotretinoin therapy, cutaneous hyperpigmentation has not, to the best of our knowledge, yet been reported as a side effect. This report presents a case of striking facial hyperpigmentation in a patient on oral isotretinoin.
Keywords: Isotretinoin